The Great Ancestors are WatchingA Cross-Cultural Study of Superior Ancestral Religion - Sheils, Dean (Sociological analysis, 1980)
Although social scientists have shown considerable interest in ancestor worship it is only in fairly recent times that “ancestor worship” has come to be seen as a category which includes several related, but different, religions. This article deals with one type of ancestor worship, superior ancestral religion. Unlike other forms of ancestor worship, superior ancestrals are thought to be able to influence the entire population of a society and not simply their own descendents. The major hypothesis tested is that belief in superior ancestrals will arise when central states organized on kinship basis are present because superior ancestral religion functions to (1) protect the interests of the society as a whole, (2) give the rulers a religious monopoly thought to be vital by the ruled, and (3) regulates the succession. It was also hypothesized that kinship states would themselves develop when societies are characterized by an intermediate level of differentiation and when the population is organized on the basis of unilineal descent, especially patrilineal descent. Data from 94 societies, most of which are included in the Human Relations Area Files, were used to test the hypotheses and the results were found to support them.